Water pollutant adsorption material and preparation method thereof

By preparing high-crystalline Beta nanomolecular sieve with iron tetraoxide and silica, a magnetic Beta nanomolecular sieve adsorbent is formed, which solves the problems of low adsorption efficiency and difficulty in regeneration of existing water pollutant adsorbents under complex water quality conditions, and achieves an efficient and environmentally friendly water pollutant removal effect.

CN119633744APending Publication Date: 2025-03-18DEZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510173702.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing water pollutant adsorbent materials show problems such as low adsorption efficiency and difficulty in regeneration under complex water quality conditions, and their environmental and health risks have not yet been fully evaluated, which may bring new environmental problems during large-scale applications.

Method used

By mixing aluminum trioxide with tetraethyl ammonium hydroxide solution and white carbon black, hydrothermal reaction and crystallization treatment, a high crystallinity Beta nanomolecular sieve was prepared, and composited with ferric tetraoxide and silica to form a magnetic Beta nanomolecular sieve adsorbent.

Benefits of technology

It has achieved efficient adsorption of organic and inorganic pollutants in water, possesses good regeneration performance and reusability, simplified the treatment process, and reduced environmental risks and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633744A_ABST
    Figure CN119633744A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of energy conservation and environmental protection, and particularly relates to a water pollutant adsorption material and a preparation method thereof. Comprising the following steps: firstly, mixing aluminum oxide and a tetraethylammonium hydroxide solution, stirring to dissolve the aluminum oxide and the tetraethylammonium hydroxide solution, then adding white carbon black, carrying out hydrothermal crystallization treatment, washing, drying and calcining to obtain a high-crystallinity Beta nano molecular sieve; then grinding the Beta nano molecular sieve and ferroferric oxide in a solid state and calcining to prepare a magnetic Beta nano molecular sieve; then adding polyether polyol P123 and a hydrochloric acid solution, dropwise adding tetraethyl orthosilicate for reaction, and drying to obtain a silicon dioxide coated magnetic Beta nano molecular sieve adsorbent; and finally adding toluene and an alkylating reagent, heating and drying to obtain the water pollution adsorption material. The adsorbent not only has efficient adsorption performance, but also has good recoverability, and can be recycled through a simple treatment process, so that resource waste is reduced, and environmental pollution is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of energy conservation and environmental protection, and particularly relates to a water pollutant adsorption material and a preparation method thereof. Background Art

[0002] In recent years, the research on water pollutant adsorption materials has made significant progress, and a variety of new adsorption materials have been developed to cope with the increasingly complex water pollution problem. 3 O 4 The @C material was prepared by a one-step solvothermal method and subjected to surface functionalization modification, showing high adsorption performance for emerging pollutants such as nanoplastics, anionic dyes and antibiotics (Ding Jie. Preparation of functionalized Fe3O4@C materials and research on their adsorption performance for pollutants in water [D]. Yancheng Institute of Technology, 2024.). In addition, new materials such as molybdenum disulfide-based aerogel composite adsorbents also showed good removal effects (Yu Taoming. Preparation of molybdenum disulfide-based aerogel composite adsorbents and research on their removal of pollutants in water [D]. Jilin: Jilin University, 2024.). The common characteristics of these materials are high specific surface area, adjustable pore structure and functionalized surface, which can effectively capture a variety of water pollutants.

[0003] Despite many advances, water pollutant adsorbent materials and their preparation methods still face some challenges. First, the selectivity, capacity and sustainability of adsorbent materials still need to be improved. Many traditional adsorbents exhibit problems such as low adsorption efficiency and difficulty in regeneration under complex water quality conditions. Secondly, although some new nanomaterials have excellent adsorption properties, their environmental and health risks have not been fully assessed, and they may bring new environmental problems when used on a large scale. In addition, the preparation process of adsorbent materials often requires complex processes and high energy consumption, which limits their widespread application in actual water treatment.

[0004] To solve the above problems, researchers are exploring a variety of strategies. On the one hand, the selectivity and capacity of adsorbents can be improved through material modification and composite formation. For example, adsorbents can be composited with other materials using nanotechnology to enhance their adsorption capacity and recyclability. On the other hand, environmentally friendly materials and green preparation processes can be developed to reduce the environmental risks and production costs of materials. In addition, a combination of various water treatment technologies, such as combining adsorption with biodegradation, membrane separation and other technologies, can achieve more efficient pollutant removal. The advancement of these research directions and strategies will help promote the development and application of water pollutant adsorption materials. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a water pollutant adsorption material and a preparation method thereof: Step 1: Mix aluminum oxide and tetraethylammonium hydroxide solution, and stir magnetically for 30 minutes at a speed of 500 r / min to completely dissolve the aluminum oxide. The mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:50-100. Step 2: Add white carbon black to the above mixed solution, the mass ratio of which is aluminum oxide: white carbon black = 1:50~300, mix them evenly, transfer them into the lining of a hydrothermal reactor, adjust the hydrothermal reactor to 160~180 ℃, and crystallize the mixture for 4~16 hours. After the crystallized product is naturally cooled to room temperature, it is washed and dried, and then calcined at 500~600 ℃ in an air atmosphere for 12 hours to obtain a Beta nano molecular sieve with high crystallinity; Step 3: solid-state grinding of high-crystalline Beta nanomolecular sieve and micron-sized ferroferric oxide for 1 to 3 hours, and calcining them at 150 to 220° C. for 3 to 6 hours in a tubular furnace in a nitrogen atmosphere to obtain a magnetic Beta nanomolecular sieve, wherein the mass ratio of high-crystalline Beta nanomolecular sieve to micron-sized ferroferric oxide is 1:0.2 to 0.5; Step 4: dissolving polyether polyol P123 in hydrochloric acid solution, adding magnetic Beta nanomolecular sieve, heating the mixture to 40-60°C and stirring at a speed of 400-800 r / min for 30-180 min, dropping tetraethyl orthosilicate, reacting it at 40°C and a speed of 400-800 r / min for 20 h, then transferring it to a reactor, placing it in a rotary oven, reacting it at 100-130°C for 20-48 hours, washing and drying to obtain a silica-coated magnetic Beta nanomolecular sieve adsorbent; Step 5: Add the silica-coated magnetic Beta nano-molecular sieve adsorbent to toluene, stir until well mixed, drop an alkylating agent into the mixture, heat it at 80°C for 12h, wash it with toluene three times, and vacuum dry it at 80°C for 10-12h to obtain a water pollution adsorption material.

[0006] Furthermore, in step 1, the concentration of the tetraethylammonium hydroxide solution is 35% to 50%.

[0007] Furthermore, the mass fraction of the hydrochloric acid solution in step 4 is 6.5% to 8.5%.

[0008] Furthermore, the alkylating agent in step five is one of vinyltrimethoxysilane and hexamethyldisilazane.

[0009] Furthermore, in step 4, the raw materials are calculated by mass ratio of magnetic Beta nanomolecular sieve: polyether polyol P123: hydrochloric acid solution: tetraethyl orthosilicate = 1:2.5~15:80~150:5~15.

[0010] Furthermore, in step 5, the raw materials are calculated by mass ratio of silica-coated magnetic Beta nano-molecular sieve adsorbent: toluene: alkylating agent = 1:80~150:8~15.

[0011] The beneficial effect of the present invention is that the preparation method of the present invention realizes the efficient conversion from raw materials to high-performance adsorption materials through the careful design of multiple steps. First, a highly crystalline Beta nanomolecular sieve is prepared by hydrothermal synthesis and crystallization treatment. This method can effectively improve the crystallinity and uniformity of the pore structure of the molecular sieve. Its high specific surface area and rich pore structure enable it to efficiently adsorb organic and inorganic pollutants in water, thereby effectively removing impurities in sewage. Beta nanomolecular sieve can remove heavy metal ions, organic matter and other harmful substances in sewage through various mechanisms such as adsorption, ion exchange and precipitation. At the same time, its good regeneration performance and reusability make it cost-effective in sewage treatment and will not cause secondary pollution.

[0012] Secondly, ferroferric oxide plays an important role and has a unique mechanism in sewage treatment. Through functional modification and composite structure design, the adsorption capacity of heavy metal ions and organic pollutants has been significantly improved. And by coating the surface of ferroferric oxide with inorganic material silica, a core-shell structure can be formed to enhance the stability of the material and the activity of the adsorption site. During the adsorption process of this composite material, heavy metal ions first move to the surface of the adsorbent through electrostatic attraction, then chemically coordinate or chelate with the surface functional groups, and finally attach to the surface of the carrier through physical adsorption to achieve efficient removal of pollutants. In addition, the magnetic properties of ferroferric oxide also allow the adsorbent to be quickly separated by a magnetic field, simplifying the treatment process and improving operating efficiency. The introduction of ferroferric oxide not only gives the material magnetism, but also forms a synergistic effect with beta nano-molecular sieves, further enhancing the adsorption capacity of pollutants. In addition, the silica coating can improve the stability and corrosion resistance of the material, while providing additional active sites for adsorption.

[0013] Finally, the alkylation treatment further optimized the surface properties of the material, making it have a stronger adsorption affinity for hydrophobic organic pollutants. This combination of multi-layer structure and multiple functions enables the material to efficiently adsorb and remove a variety of pollutants in water, including organic matter, heavy metal ions, etc.

[0014] This new adsorbent material has significant application potential in the field of water pollution control. Its high adsorption performance and magnetic separation characteristics enable it to efficiently remove pollutants from water, while simplifying the recovery and reuse process of the adsorbent. In addition, the preparation method of this material is relatively simple, the raw material source is wide, the cost is low, and it is suitable for large-scale production and application. Moreover, the adsorbent not only has efficient adsorption performance, but also has good recyclability, and can be recycled through a simple treatment process, thereby reducing resource waste and reducing environmental pollution. In practical applications, this material can be used to treat industrial wastewater, domestic sewage and contaminated groundwater, and has a significant effect on removing difficult-to-degrade organic pollutants and heavy metal ions. With further optimization of technology and reduction of cost, this material is expected to be more widely used in the field of water treatment, providing strong support for environmental protection and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a scanning electron microscope image of the highly crystalline Beta nanomolecular sieve prepared in Example 1; Figure 2 XRD diagram of the silica-coated magnetic Beta nanomolecular sieve adsorbent prepared in Examples 1 to 3. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0017] The water pollutant adsorption material and the preparation method thereof provided by the present invention are specifically described below through examples.

[0018] Example 1

[0019] Step 1: Mix aluminum oxide and tetraethylammonium hydroxide solution (35%), and stir magnetically for 30 minutes at a speed of 500 r / min to completely dissolve the aluminum oxide. The mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:100. Step 2: Add white carbon black to the above mixed solution in a mass ratio of aluminum oxide: white carbon black = 1:50, mix them evenly, transfer them into the lining of a hydrothermal reactor, adjust the hydrothermal reactor to 165 ° C, and crystallize the mixture for 12 hours. After the crystallization product is naturally cooled to room temperature, it is washed and dried, and then calcined at 550 ° C in an air atmosphere for 12 hours to obtain a Beta nano molecular sieve with high crystallinity; Step 3: solid-state grinding of high-crystalline Beta nanomolecular sieve and micron-sized ferroferric oxide for 1.5 hours, calcining at 200° C. for 5 hours in a tubular furnace in a nitrogen atmosphere to obtain a magnetic Beta nanomolecular sieve, wherein the mass ratio of high-crystalline Beta nanomolecular sieve to micron-sized ferroferric oxide is 1:0.4; Step 4: dissolve polyether polyol P123 in hydrochloric acid solution (mass fraction of 6.6%), add magnetic Beta nanomolecular sieve, heat the mixture to 50°C and stir at a speed of 500r / min for 120min, drop tetraethyl orthosilicate, react it at 40°C and a speed of 550r / min for 20 hours, then transfer it to a reactor, place it in a rotary oven, react it at 120°C for 20 hours, wash and dry to obtain a silica-coated magnetic Beta nanomolecular sieve adsorbent, and the raw materials are calculated by mass ratio: magnetic Beta nanomolecular sieve: polyether polyol P123: hydrochloric acid solution: tetraethyl orthosilicate = 1:3.2:125:8; Step 5: Add the silica-coated magnetic Beta nano-molecular sieve adsorbent to toluene, stir until well mixed, drop vinyltrimethoxysilane, heat it at 80°C for 12h, wash it with toluene 3 times, and vacuum dry it at 80°C for 12h to obtain the water pollution adsorption material. The raw materials are calculated by mass ratio: silica-coated magnetic Beta nano-molecular sieve adsorbent: toluene: alkylating agent = 1:100:10.

[0020] Figure 1 This is a scanning electron microscope image of the highly crystalline Beta nanomolecular sieve prepared in step 2. As shown in the figure, the molecular sieve presents a uniform nanocrystalline grain structure with a grain size of about 300 nm. This highly crystalline Beta nanomolecular sieve has good dispersibility, which is conducive to the dispersion of ferroferric oxide by solid-state grinding in the next step. During the solid-state grinding process, the uniform nanocrystalline grain structure can ensure that the ferroferric oxide particles are in full contact with the Beta nanomolecular sieve, thereby achieving efficient physical mixing and chemical compounding. This uniform dispersion not only helps to improve the adsorption performance of the composite material, but also enhances its magnetic separation ability, so that it can show better performance in subsequent water treatment applications. In addition, the stability and durability exhibited by the highly crystalline Beta nanomolecular sieve during the grinding process further ensure the structural integrity of the composite material and provide a solid foundation for the preparation of high-performance adsorbents.

[0021] exist Figure 2In the XRD spectrum of the water pollution adsorbent prepared in Example 1, the XRD spectrum only shows the amorphous peak of silica and does not show the characteristic peak of Beta molecular sieve, which indicates that the silica shell wraps the Beta molecular sieve well. This good wrapping effect not only helps to enhance the stability of the material, but also effectively prevents the Beta molecular sieve from structural damage or performance degradation during subsequent treatment. In addition, the uniform wrapping of the silica shell also provides an additional protective layer for the adsorbent material, enabling it to exhibit better durability and adsorption performance in a complex water pollution environment.

[0022] Example 2

[0023] Step 1: Mix aluminum oxide and tetraethylammonium hydroxide solution (40%), and stir magnetically for 30 minutes at a speed of 500 r / min to completely dissolve the aluminum oxide. The mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:75. Step 2: Add white carbon black to the above mixed solution in a mass ratio of aluminum oxide: white carbon black = 1:85, mix them evenly, transfer them into the lining of a hydrothermal reactor, adjust the hydrothermal reactor to 165 ° C, and crystallize the mixture for 12 hours. After the crystallized product is naturally cooled to room temperature, it is washed and dried, and then calcined at 550 ° C in an air atmosphere for 12 hours to obtain a Beta nano molecular sieve with high crystallinity; Step 3: solid-state grinding of high-crystalline Beta nanomolecular sieve and micron-sized ferroferric oxide for 1.5 hours, and calcining the mixture at 200° C. for 5 hours in a tubular furnace in a nitrogen atmosphere to obtain a magnetic Beta nanomolecular sieve, wherein the mass ratio of high-crystalline Beta nanomolecular sieve to micron-sized ferroferric oxide is 1:0.5; Step 4: dissolve polyether polyol P123 in hydrochloric acid solution (mass fraction of 7.1%), add magnetic Beta nanomolecular sieve, heat the mixture to 50°C and stir at a speed of 500r / min for 120min, drop tetraethyl orthosilicate, react it at 40°C and a speed of 550r / min for 20 hours, then transfer it to a reactor, place it in a rotary oven, react it at 120°C for 20 hours, wash and dry to obtain a silica-coated magnetic Beta nanomolecular sieve adsorbent, and the raw materials are calculated by mass ratio: magnetic Beta nanomolecular sieve: polyether polyol P123: hydrochloric acid solution: tetraethyl orthosilicate = 1:3.5:132:9.5; Step 5: Add the silica-coated magnetic Beta nano-molecular sieve adsorbent to toluene, stir until well mixed, drop vinyltrimethoxysilane, heat it at 80°C for 12h, wash it with toluene 3 times, and vacuum dry it at 80°C for 12h to obtain the water pollution adsorption material. The raw materials are calculated by mass ratio: silica-coated magnetic Beta nano-molecular sieve adsorbent: toluene: alkylating agent = 1:110:10.

[0024] exist Figure 2 In the XRD spectrum of the water pollution adsorbent prepared in Example 2, the XRD spectrum only shows the amorphous peak of silica and does not show the characteristic peak of Beta molecular sieve, which indicates that the silica shell wraps the Beta molecular sieve well. This good wrapping effect not only helps to enhance the stability of the material, but also effectively prevents the Beta molecular sieve from structural damage or performance degradation during subsequent treatment. In addition, the uniform wrapping of the silica shell also provides an additional protective layer for the adsorbent material, allowing it to show better durability and adsorption performance in a complex water pollution environment.

[0025] Example 3

[0026] Step 1: Mix aluminum oxide and tetraethylammonium hydroxide solution (40%), and stir magnetically for 30 minutes at a speed of 500 r / min to completely dissolve the aluminum oxide. The mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:80. Step 2: Add white carbon black to the above mixed solution in a mass ratio of aluminum oxide: white carbon black = 1:250, mix them evenly, transfer them into the lining of a hydrothermal reactor, adjust the hydrothermal reactor to 165 ° C, and crystallize the mixture for 12 hours. After the crystallization product is naturally cooled to room temperature, it is washed and dried, and then calcined at 550 ° C in an air atmosphere for 12 hours to obtain a Beta nano molecular sieve with high crystallinity; Step 3: solid-state grinding of high-crystalline Beta nanomolecular sieve and micron-sized ferroferric oxide for 1.5 hours, calcining at 200° C. for 5 hours in a tubular furnace in a nitrogen atmosphere to obtain a magnetic Beta nanomolecular sieve, wherein the mass ratio of high-crystalline Beta nanomolecular sieve to micron-sized ferroferric oxide is 1:0.4; Step 4: dissolve polyether polyol P123 in hydrochloric acid solution (mass fraction of 7.5%), add magnetic Beta nanomolecular sieve, heat the mixture to 50°C and stir at a speed of 500r / min for 120min, drop tetraethyl orthosilicate, react it at 40°C and a speed of 550r / min for 20 hours, then transfer it to a reactor, place it in a rotary oven, react it at 120°C for 20 hours, wash and dry to obtain a silica-coated magnetic Beta nanomolecular sieve adsorbent, and the raw materials are calculated by mass ratio: magnetic Beta nanomolecular sieve: polyether polyol P123: hydrochloric acid solution: tetraethyl orthosilicate = 1:5.3:140:10.2; Step 5: Add the silica-coated magnetic Beta nano-molecular sieve adsorbent to toluene, stir until well mixed, drop vinyltrimethoxysilane, heat it at 80°C for 12h, wash it with toluene 3 times, and vacuum dry it at 80°C for 12h to obtain the water pollution adsorption material. The raw materials are calculated by mass ratio: silica-coated magnetic Beta nano-molecular sieve adsorbent: toluene: alkylating agent = 1:120:11.5.

[0027] exist Figure 2 In the XRD spectrum of the water pollution adsorbent prepared in Example 3, the XRD spectrum only shows the amorphous peak of silica and does not show the characteristic peak of Beta molecular sieve, which indicates that the silica shell wraps the Beta molecular sieve well. This good wrapping effect not only helps to enhance the stability of the material, but also effectively prevents the Beta molecular sieve from structural damage or performance degradation during subsequent treatment. In addition, the uniform wrapping of the silica shell also provides an additional protective layer for the adsorbent material, allowing it to show better durability and adsorption performance in a complex water pollution environment.

[0028] Comparative Example 1 Step 1: Mix aluminum oxide and tetraethylammonium hydroxide solution (35%), and stir magnetically for 30 minutes at a speed of 500 r / min to completely dissolve the aluminum oxide. The mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:100. Step 2: Add white carbon black to the above mixed solution in a mass ratio of aluminum oxide: white carbon black = 1:85. After mixing them evenly, transfer them into the lining of a hydrothermal reactor. Adjust the hydrothermal reactor to 165°C and crystallize the mixture. After crystallization for 12 hours, cool the crystallized product naturally to room temperature, wash and dry it, and calcine it at 550°C in an air atmosphere for 12 hours to obtain a highly crystalline Beta nanomolecular sieve.

[0029] Comparative Example 2 Step 1: Mix aluminum oxide and tetraethylammonium hydroxide solution (35%), and stir magnetically for 30 minutes at a speed of 500 r / min to completely dissolve the aluminum oxide. The mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:100. Step 2: Add white carbon black to the above mixed solution in a mass ratio of aluminum oxide: white carbon black = 1:85, mix them evenly, transfer them into the lining of a hydrothermal reactor, adjust the hydrothermal reactor to 165 ° C, and crystallize the mixture for 12 hours. After the crystallized product is naturally cooled to room temperature, it is washed and dried, and then calcined at 550 ° C in an air atmosphere for 12 hours to obtain a Beta nano molecular sieve with high crystallinity; Step 3: Solid-state grinding of high-crystalline Beta nanomolecular sieve and micron-sized ferroferric oxide for 1.5 hours, calcining at 200°C for 5 hours in a tubular furnace in a nitrogen atmosphere, to obtain a magnetic Beta nanomolecular sieve, wherein the mass ratio of high-crystalline Beta nanomolecular sieve to micron-sized ferroferric oxide is 1:0.4.

[0030] Comparative Example 3 Step 1: Mix aluminum oxide and tetraethylammonium hydroxide solution (35%), and stir magnetically for 30 minutes at a speed of 500 r / min to completely dissolve the aluminum oxide. The mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:100. Step 2: Add white carbon black to the above mixed solution in a mass ratio of aluminum oxide: white carbon black = 1:85, mix them evenly, transfer them into the lining of a hydrothermal reactor, adjust the hydrothermal reactor to 165 ° C, and crystallize the mixture for 12 hours. After the crystallized product is naturally cooled to room temperature, it is washed and dried, and then calcined at 550 ° C in an air atmosphere for 12 hours to obtain a Beta nano molecular sieve with high crystallinity; Step 3: Dissolve polyether polyol P123 in hydrochloric acid solution (mass fraction of 6.6%), add highly crystalline Beta nanomolecular sieve, heat the mixture to 50°C and stir at 500r / min for 120min, drop tetraethyl orthosilicate, react it at 40°C and 550r / min for 20 hours, then transfer it to a reactor, place it in a rotary oven, react it at 120°C for 20 hours, wash and dry to obtain a silica-coated Beta nanomolecular sieve adsorbent. The raw materials are calculated by mass ratio: highly crystalline Beta nanomolecular sieve: polyether polyol P123: hydrochloric acid solution: tetraethyl orthosilicate = 1:3:120:7.5.

[0031] Adsorption performance test: 40 mg of water-contaminated adsorbent material was added to 50 mL of adsorption pollutant solution (initial pollutant solution concentration was 300 mg / L, adsorption was performed at 25°C for 12 h). The adsorption experiment was carried out in an oscillating oven at 100 rpm. During the adsorption process, the pollutant solution was collected regularly. Congo red (488 nm), tetracycline (360 nm) and Cu (64-nitrogen) were measured using a UV-Vis spectrophotometer (UV-Vis, UH5300). 2+ (452 nm) solution concentration. Calculate the adsorption performance of the sample in the pollutant solution:

[0032] In the formula, q e (mg / g) is the equilibrium adsorption capacity of the sample for pollutants, C 0 (mg / L) is the initial adsorption concentration, C e (mg / L) is the adsorption concentration after a period of time, m (g) is the weight of the adsorbent used, and V (L) is the volume of the solution. The adsorption data of the pollutants in the embodiments and comparative examples are shown in Table 1.

[0033] Table 1 Pollutant adsorption capacity of Examples 1 to 3 and Comparative Examples 1 to 3

[0034] From the data in Table 1, it can be seen that Example 2 has no significant effect on Congo red, tetracycline and Cu² + All of them have the largest adsorption capacity, which shows that they show excellent comprehensive performance in treating multiple pollutants. In contrast, although Example 1 and Example 3 are slightly inferior in the adsorption of certain pollutants, their adsorption capacity for the three pollutants exceeds that of the comparative example, showing obvious performance advantages. Overall, the excellent performance of Example 2 makes it have greater potential in actual sewage treatment applications, especially in the treatment of complex wastewater, it can more efficiently remove multiple pollutants.

Claims

1. A method for preparing a water pollutant adsorbent material, characterized in that: The following steps are included: Step 1: Mix aluminum oxide and tetraethylammonium hydroxide solution, and stir magnetically for 30 minutes at a speed of 500 r / min to completely dissolve the aluminum oxide. The mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:50-100. Step 2: Add white carbon black to the above mixed solution in a mass ratio of aluminum oxide: white carbon black = 1:50~300, mix them evenly, transfer them into the lining of a hydrothermal reactor, adjust the hydrothermal reactor to 160~180°C, and crystallize the mixture for 4~16h. After the crystallized product is naturally cooled to room temperature, it is washed and dried, and then calcined at 500~600°C in an air atmosphere for 12h to obtain a Beta nano molecular sieve with high crystallinity; Step 3: solid-state grinding of high-crystalline Beta nanomolecular sieve and micron-sized ferroferric oxide for 1 to 3 hours, and calcining them at 150 to 220° C. for 3 to 6 hours in a tubular furnace in a nitrogen atmosphere to obtain a magnetic Beta nanomolecular sieve, wherein the mass ratio of high-crystalline Beta nanomolecular sieve to micron-sized ferroferric oxide is 1:0.2 to 0.5; Step 4: dissolving polyether polyol P123 in hydrochloric acid solution, adding magnetic Beta nanomolecular sieve, heating the mixture to 40-60°C and stirring at a speed of 400-800 r / min for 30-180 min, dropping tetraethyl orthosilicate, reacting it at 40°C and a speed of 400-800 r / min for 20 h, then transferring it to a reactor, placing it in a rotary oven, reacting it at 100-130°C for 20-48 hours, washing and drying to obtain a silica-coated magnetic Beta nanomolecular sieve adsorbent; Step 5: Add the silica-coated magnetic Beta nano-molecular sieve adsorbent to toluene, stir until well mixed, drop an alkylating agent into the mixture, heat it at 80°C for 12h, wash it with toluene three times, and vacuum dry it at 80°C for 10-12h to obtain a water pollution adsorption material.

2. The method for preparing a water pollutant adsorbent material according to claim 1, characterized in that: The concentration of the tetraethylammonium hydroxide solution in step 1 is 35% to 50%.

3. The method for preparing a water pollutant adsorbent material according to claim 1, characterized in that: The mass fraction of the hydrochloric acid solution in step 4 is 6.5% to 8.5%.

4. The method for preparing a water pollutant adsorbent material according to claim 1, characterized in that: The alkylating agent in step 5 is vinyltrimethoxysilane or hexamethyldisilazane.

5. The method for preparing a water pollutant adsorbent material according to claim 1, characterized in that: The raw materials in step 4 are calculated by mass ratio as follows: magnetic Beta nanomolecular sieve: polyether polyol P123: hydrochloric acid solution: tetraethyl orthosilicate = 1:2.5~15:80~150:5~15.

6. The method for preparing a water pollutant adsorbent material according to claim 1 or 4, characterized in that: In step 5, the raw materials are calculated by mass ratio of silica-coated magnetic Beta nano-molecular sieve adsorbent: toluene: alkylating agent = 1:80~150:8~15.

7. A water pollutant adsorbing material, characterized in that: The method is prepared by any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation of magnetic nano-adsorbent and application of magnetic nano-adsorbent in composite waste water treatment

    CN107149924A

  • Preparation method of amino modified material composite molecular sieve

    CN108793188A

  • Method for preparing Ti-beta molecular sieve nanocrystals

    CN110422855A

  • Preparation method and application of porous zeolite adsorbent

    CN114011390A

  • Method for efficiently preparing ethyl chrysanthemate by using Beta / CuCl nano molecular sieve catalyst

    CN119330826A